2013
DOI: 10.1016/j.resp.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane and ketamine anesthesia have different effects on ventilatory pattern variability in rats

Abstract: We hypothesize that isoflurane and ketamine impact ventilatory pattern variability (VPV) differently. Adult Sprague-Dawley rats were recorded in a whole-body plethysmograph before, during and after deep anesthesia. VPV was quantified from 60-s epochs using a complementary set of analytic techniques that included constructing surrogate data sets that preserved the linear structure but disrupted nonlinear deterministic properties of the original data. Even though isoflurane decreased and ketamine increased respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…As for the effects on respiration, isoflurane anesthesia was found to reduce respiratory rate in laboratory animals including rats [9], mice [8, 39], and rabbits [16]. In this study, we confirmed that isoflurane, as its inhalation concentration increased, decreased the respiratory rate in SHR/Izm, WKY/Izm, and Crl:CD (SD) rats.…”
Section: Discussionsupporting
confidence: 74%
“…As for the effects on respiration, isoflurane anesthesia was found to reduce respiratory rate in laboratory animals including rats [9], mice [8, 39], and rabbits [16]. In this study, we confirmed that isoflurane, as its inhalation concentration increased, decreased the respiratory rate in SHR/Izm, WKY/Izm, and Crl:CD (SD) rats.…”
Section: Discussionsupporting
confidence: 74%
“…1 E) was a significant difference detected. A possible reason for that could be the loss of heart rate- and breathing rate-response due to the adjustment of anaesthesia with isoflurane 24 , 25 . Interestingly, the animals of the treatment group stabilized their body core temperature after the period of hemodilution, whereas the animals of the control group showed a decrease in temperature (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Performing our recordings under anaesthesia could minimise the EMG output achieved and, subsequently, underestimate the scale of recovery achieved. 10,60 However, any respiratory depressant effect was minimal as our recordings were performed under light ketamine-xylazine anaesthesia 61 and significant ipsilateral hemidiphragm recovery has been previously reported in contused animals assessed under similar conditions of anaesthesia. 12,17 There is compensatory plasticity demonstrated within our control treated animals shown through the increased activity of the contralateral hemidiaphragm and modulation of respiratory frequency.…”
Section: Compromised Diaphragm Activity Is Persistent Overtimementioning
confidence: 69%